DEVELOPMENT OF ELECTRONIC MODULES BASED INKUIRI ON PHYSICS LESSON MATERIALS OF TEMPERATURE AND KALOR IN SECONDARY SCHOOL - Biqom Helda Zia; Sardianto Markos Siahaan; Nyayu Khodijah (Sriwijaya University Learning and Education International Conference, 2018)
Physic electronic module inquiry-based in the main subject of temperature and heat valid, practical and effectiveness to the learning result for senior high school were successfully developed. The research method used development research with the Hannafin and Pack model and Tessmer evaluation. Stages performed in this study include the planning stage, the design stage, and the development stage. In the evaluation phase using Tessmer's evaluation, which consists of 5 stages: self-evaluation, expert evaluation, one to one evaluation, small group evaluation and field test. The subjects of the study were students of science class XI Muhammadiyah Senior High School 3 Palembang. The validity of this electronic module is assessed by four experts namely material experts, media experts, software experts and design learning experts. Expert or validator results obtained by 0.78 from material experts, 0.82 from media experts, from software experts 0.87, and 0.75 from design learning experts, so that developed electronic modules are valid and can be tested as suggested.The practicality of electronic modules can be seen from the quantitative assessment of learners from one to one evaluation trial consisting of 3 (three) students who have high ability, moderate and low. Then a small group evaluation trial consisting of 9 (nine) students. The average result of the quantitative assessment of the practicality of the electronic module is examined in one-to-one evaluation and small group evaluation of 0.84 with very high category, so it can be concluded that practical module is very practical in learning. The effectiveness of this electronic module is apparent from the learning outcomes which show an increase with N-gain of 0,66 which is included. This shows that physics electronic modules inquiry-based on temperature and heat materials that have been developed have effectiveness to learners' learning outcomes.